Avaliação do efeito probiótico de Saccharomyces cerevisiae UFMG A- 905 em um modelo murino de alergia alimentar - Vivian Correia Miranda (2019)
The increased prevalence of food allergy cases has become an obstacle to public health leading to a relevant economic cost for the health care system. Food allergy is triggered when there is an abnormal activation of the immune system by food allergens. Symptoms of food allergy can range from abdominal pain to the most severe anaphylactic cases. One of the alternative therapies that have been studied is the use of probiotics, given its proven immunomodulatory proprieties. Therefore, the aim of this study was to evaluate the probiotic effect of S. cerevisiae UFMG A-905 in an in vivo model of food allergy, analyzing clinical, histological, immunological and microbiological parameters. In addition, the dose-response, the effect of the viability of the yeast and the supernatant of the culture were also evaluated. For this purpose, mice were sensitized with ovalbumin (OVA) (day 0). After 14 days they received a booster. The control group received only the adjuvant with saline by day 0 and only saline on 14th day. On 18th day, mice received daily the respective treatment of S. cerevisiae UFMG A-905 or its supernatant, until the end of the experiment (28th day). From 21st day until the end the mice were challenged with a diet containing OVA. On 28th day mice were euthanized. Oral administration of viable S. cerevisiae UFMG A- 905 led to a significant attenuation of the degree of tissue injury, and in addition, it promotes a significant reduction of MPO levels, this reduction presenting a dosedependent profile. Furthermore, the treatment promoted a tendency to reduce approximately 50% of eosinophil recruitment, attenuating the inflammatory infiltrate. In addition, the present study showed that the treatment promoted a significant decrease of the cytokine IL-17 levels. Furthermore, the administration of the supernatant of the viable culture of the yeast also promoted a significant reduction of the MPO levels. However, considering the systemic parameters IgE e IgG anti-OVA, which are essentials for the triggering of the allergic process, there was no effect, suggesting that the yeast promotes a local but not systemic effect, in the model evaluated. Therefore, oral administration of S. cerevisiae UFMG A-905 led to a local, dose-dependent probiotic effect that depends on the viability of the yeast.